Australian unemployed workers' experiences of being parked and creamed by employment providers. Issue 4 (4th September 2020) - O'Halloran, David; Farnworth, Louise; Thomacos, Nikos
Abstract: This research examines the experiences of unemployed workers who report they have been parked or creamed by their employment services provider. Using focus group methodology, the research findings suggest that the experiences of being parked or creamed do not simply reflect quantitative metrics such as appointment frequency, and are experienced primarily as reflections of the quality of the transactions that occur in appointments. The findings suggest that parking and creaming are pervasive with harmful consequences for unemployed workers. Parking, on the one hand, appears to exacerbate the scarring effect of unemployment. Creaming, on the other hand, is not experienced as a benefit because rapid placement into employment is likely to be directed toward underemployment or precarious employment rather than sustainable employment. A second type of creaming is also described, where providers seek to take credit, sometimes coercively, for unemployed workers finding their own jobs. The findings also suggest that the Department of Employment's actions to date to curb the practices have not been successful and could be improved if unemployed workers were more clearly recognised as having a stake in the provision of high‐quality employment services and given suitable mechanisms to identify and select providers that will not park or cream them.